Tratamento homeopático na remediação de solos contaminados por metais cultivados com soja e trigo - Santos, Marcelo Gonçalves dos (2016)
This study evaluated the remediation of soils contaminated with Cd and Pb with different dynamizations of homeopathic medicine Nux vomica and development of soybean and wheat grown in these soils. Therefore, we developed two experiments. The soils were contaminated with metals using CdCl2 and PbCl2H2O salts in three doses, based on the resolution of the research values (VI) of resolution No. 420 of CONAMA (dose 1 - value preexisting in the soil; dose 2 the VI and dose 3 - three times the VI) resulting in 0; 3 and 9 mg kg-1 for Cd, 89; 180 and 540 mg kg-1 for Pb. The dynamizations of homeopathic medicine Nux vomica utilized were 0, 12, 24, 48, 96, 200 and 400CH (centesimal hahnemanianna), being the witness (0CH) distilled water. The applications of the medicament in soil were days before and at sowing, while plants were applied in intervals of 14 days until complete the cycle. It was evaluated the development and gas exchange during the crop growing season. At flowering were evaluated the nutritional composition of plants determining the levels of N, P, K, Ca, Mg, Cu, Zn, Fe, Mn as well as Cd and Pb. At the end of the cycle the production of components were quantified. Subsequently, the plants were sectioned in plant organs and the bioavailability of the metals in their tissues. In soybean plants the dynamizations of homeopathic medicine Nux vomica changed height, stem diameter and gas exchange, and the soil contamination with Cd and Pb changed all variables. In wheat plants, homeopathic medicine interfered only in height and diameter of the stem being that contamination by Cd and Pb did not interfere with gas exchange, but negatively affected the development, mineral nutrition, roots system and plant productivity. It is concluded that the homeopathic medicine Nux vomica is effective for plant development of soybean and wheat grown in soil contaminated with Cd and Pb, however did not interfere in phytoavailability of metals to plants